let x1, x2 be FinSequence of COMPLEX ; :: thesis: ( len x1 = len x2 implies (x1 + x2) *' = (x1 *') + (x2 *') )
reconsider x9 = x1 as Element of (len x1) -tuples_on COMPLEX by FINSEQ_2:92;
reconsider y9 = x2 as Element of (len x2) -tuples_on COMPLEX by FINSEQ_2:92;
reconsider x3 = x1 *' as Element of (len (x1 *')) -tuples_on COMPLEX by FINSEQ_2:92;
reconsider x4 = x2 *' as Element of (len (x2 *')) -tuples_on COMPLEX by FINSEQ_2:92;
assume A1: len x1 = len x2 ; :: thesis: (x1 + x2) *' = (x1 *') + (x2 *')
then A2: len (x1 + x2) = len x1 by Th6;
A3: ( len x1 = len (x1 *') & len x2 = len (x2 *') ) by Def1;
A4: now :: thesis: for i being Nat st 1 <= i & i <= len ((x1 + x2) *') holds
((x1 + x2) *') . i = (x3 + x4) . i
let i be Nat; :: thesis: ( 1 <= i & i <= len ((x1 + x2) *') implies ((x1 + x2) *') . i = (x3 + x4) . i )
A5: i in NAT by ORDINAL1:def 12;
assume that
A6: 1 <= i and
A7: i <= len ((x1 + x2) *') ; :: thesis: ((x1 + x2) *') . i = (x3 + x4) . i
A8: i <= len (x1 + x2) by ;
hence ((x1 + x2) *') . i = ((x1 + x2) . i) *' by
.= ((x9 . i) + (y9 . i)) *' by A1, A5, Th14
.= ((x1 . i) *') + ((x2 . i) *') by COMPLEX1:32
.= ((x1 *') . i) + ((x2 . i) *') by A2, A6, A8, Def1
.= ((x1 *') . i) + ((x2 *') . i) by A1, A2, A6, A8, Def1
.= (x3 + x4) . i by A1, A3, A5, Th14 ;
:: thesis: verum
end;
len ((x1 *') + (x2 *')) = len x1 by A1, A3, Th6;
hence (x1 + x2) *' = (x1 *') + (x2 *') by A4, A2, Def1; :: thesis: verum